Mediating effect of AI attitudes and AI literacy on the relationship between career self-efficacy and job-seeking anxiety - Ruihua Li; Sha Ouyang; Jianwei Lin (BMC Psychology)
Abstract As artificial intelligence (AI) technology quickly grows, college students have new worries and fears. Using Marx’s theory of labour alienation, this study explores the complex relationship between college students’ job-seeking anxiety (JSA) and career self-efficacy (CSE) in the context of the AI era. A structural equation modeling (SEM) study of data from 455 Chinese students indicates that CSE adversely affects JSA. Moreover, AI attitudes (AIA) and AI literacy (AIL) play significant mediating roles in the relationship between career self-efficacy (CSE) and job-specific anxiety (JSA). Specifically, these factors help explain how CSE influences JSA by fostering positive perceptions of AI and improving students’ understanding of AI technologies. The findings underscore the importance of cultivating positive attitudes toward AI, enhancing AI literacy, and strengthening career self-efficacy to reduce job-seeking anxiety and better prepare students for the challenges of an AI-driven job market. These observations provide significant implications for educators and policymakers in developing interventions to enhance students’ career preparedness and protect their mental health during technological changes.